2012
DOI: 10.3109/14767058.2011.587060
|View full text |Cite
|
Sign up to set email alerts
|

Rate of preterm birth in pregnant women with vitamin E treatment: a population-based study

Abstract: The study showed nearly 30% reduction in preterm births of pregnant women with vitamin E treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Additionally, in a study in the United States (n = 9968; n = 4992 in the vitamin group and n = 4976 in the placebo group), where at baseline pregnant women were taking 22 IU vitamin E in a daily multivitamin (equal to the RDA), additional vitamin E supplements (400 IU) were not beneficial in reducing the risk of preterm births (102). By contrast, vitamin E supplements were associated with a decreased incidence of preterm births in a Hungarian population study (103). Although it is apparent that the vitamin E status of pregnant women must be adequate to successfully bear a child, these findings suggest that vitamin E supplements in excess of the RDA to adequately nourished women do not provide additional benefits.…”
Section: Consequences Of Low Vitamin E Statusmentioning
confidence: 99%
“…Additionally, in a study in the United States (n = 9968; n = 4992 in the vitamin group and n = 4976 in the placebo group), where at baseline pregnant women were taking 22 IU vitamin E in a daily multivitamin (equal to the RDA), additional vitamin E supplements (400 IU) were not beneficial in reducing the risk of preterm births (102). By contrast, vitamin E supplements were associated with a decreased incidence of preterm births in a Hungarian population study (103). Although it is apparent that the vitamin E status of pregnant women must be adequate to successfully bear a child, these findings suggest that vitamin E supplements in excess of the RDA to adequately nourished women do not provide additional benefits.…”
Section: Consequences Of Low Vitamin E Statusmentioning
confidence: 99%
“…The biological function of vitamin E is an antioxidant that protects tissues and cells from the damaging effect of reactive oxygen species [32]. It may prevent preterm birth by improving the health of the cervix and inhibiting premature cervical remodeling and provide beneficial effect for placenta function [30,33]. …”
Section: Discussionmentioning
confidence: 99%
“…Finally, the most important result of our study is that we have shown that glutathione was able to inhibit all LPS‐induced labor‐associated features in the human myometrium, as well as to prevent inflammation‐induced preterm labor in mice. To date, only a few clinical trials have assessed the effect of antioxidant molecules on pregnancy‐related disorders, and only vitamin E and C have been tested but with disappointing results (6163). We also tested the effect of vitamin E in our model and found that this vitamin, which does not cross biologic membranes (29), only blocked features related to MCs, while no protective effect was observed on macrophage activation, which may explain the poor clinical effects reported.…”
Section: Discussionmentioning
confidence: 99%